Legal and Economic Problems of the Governmental Regulation of Renewable Energy Sources Usage and Development in the Republic of Kazakhstan - TELEUYEV, Galym; YERKІNBAYEVA, Lazzat; BEKTURGANOV, Abdimanap (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The paper shows that ensuring energy security as an important component of national security is a high-priority task of the state in the modern context. The authors founded out that development of the area of renewable alternative power is one of the major directions of ensuring the required level of energy security. The paper revels that ensuring sustainable functioning of this area is impossible without proper scientific and theoretical rationale and identifying corresponding methodological approaches to formulation of the content of general categories of the government regulation of alternative energy development.
Keywords: renewable energy sources; government regulation; alternative development; economical basis; recycling